Examining solar flare effects on earth’s ionosphere using ground-based measurements - Nurul Shazana Abdul Hamid,; Raja Adibah Raja Halim,; Idahwati Sarudin,; Yoshikawa, Akimasa; Fujimoto, Akiko (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study investigated the simultaneous effects of solar flares (SFs) on both the D and E layers of Earth’s ionosphere. The analysis focused on the M and X-class SFs that occurred during the 24th solar cycle as these two classes of SFs are known to produce significant effects on Earth’s environment, particularly during the daytime period. The data utilized to detect the SF events in this study were ground-based magnetometer data from the equatorial regions. Effects of the selected SF events on the E layer were investigated based on the EUEL index constructed using the geomagnetic data. Meanwhile, the changes in the strength of radio VLF signals in the D ionospheric layer during the selected SF events were monitored using Sudden Ionospheric Disturbance (SID) data. Two case studies were performed which consisted of four SF events from a total of 23 events that were detected by geomagnetic data during the period of study. Further analysis on the selected SF events showed the common effects of SFs on the D layer, which is the increment on the VLF signal measured from the SID stations although a different response was detected in the EUEL index variations. This indicates that the VLF signal always shows an increment even though a decrement in the ionization of the E layer occurs as a result of the SF events. The difference in responses could be attributed to the distinct changes in electron density of both layers during the SF occurrence. Further studies are needed to elucidate the underlying mechanism responsible for this unique response, utilizing appropriate parameters such as total electron content, as well as the electron density data to thoroughly analyze the ionospheric response during SF events.